Exploring Raised Cosine Filtering for Signal Integrity and ISI Mitigation in Digital Communication Systems’ - Mst Jannatul Kobra; Md Owahedur Rahman (Universitas Komputer Indonesia, 2026)
In high-speed networks such as 4G/5G, bandwidth constraints remain a major challenge for digital communication systems, where Inter-Symbol Interference (ISI) significantly degrades signal quality. This study investigates the application of raised cosine filtering to mitigate ISI and enhance signal integrity across several modulation schemes, including BPSK, QPSK, and M-PSK. MATLAB simulations were conducted using roll-off factor values ranging from 0.1 to 0.9, and system performance was evaluated in terms of Bit Error Rate (BER), Peak-to-Average Power Ratio (PAPR), and signal quality represented by eye diagrams. The results indicate that higher roll-off factors provide better ISI mitigation and improved signal clarity, although at the expense of increased bandwidth consumption. The findings highlight the trade-off between bandwidth efficiency and ISI reduction, which is essential for designing optimized filters in modern high-speed communication systems. These results can support the development of more efficient filtering techniques for practical communication networks such as 4G/5G and Wi-Fi, thereby providing valuable insights for communication system designers.